Development of a Simple and Low-Cost Light Diffraction Props for Teaching and Learning Optics during Covid-19 Outbreak - Kartini Herlina; B. Anggit Wicaksono; Doni Andra; I Dewa Putu Nyeneng (Jurnal Pendidikan MIPA, 2022)
The Covid-19 pandemic forces the learning process to be carried out in a blended learning manner that combines face-to-face and synchronous learning.This study aims to share the implementation of experiments that we have carried out during the Covid-19 pandemic, especially on optics material for high schools involving prospective physics teacher students. This study uses a descriptive research method with the research subject being Physics Education students, FKIP University of Lampung, with a sample of 2017 Physics Education students who are taking Optics lectures.The results of this study are in the form of optical learning media that have been designed by students while attending lectures with distinctive characteristics made from low cost material and using simple technologies. This study proves that physics experiments can be carried out by utilizing learning media in the form of low-cost material teaching aids. In addition, physics experiments can be carried out directly without a complicated preparation. Learning activities that utilize this kind of teaching aids will certainly train students' science process skills, procedural knowledge and conceptual knowledge that is improved through hands-on activities and mind-on activities during the learning process. Keywords: blended learning, teaching aids, science process skills, hands-on activity, mind-on activity DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp437-447